Perceived stress, work-family conflict and work engagement as correlates of psychological well-being of working nursing mothers in Ibadan metropolis (2016)
The study examined the influence of perceived stress, work-family conflict and work engagement on the psychological well-being of working nursing mothers in Ibadan metropolis, Oyo state. Descriptive survey method was employed for this study. A sample of three hundred and fourteen working nursing mothers was randomly selected among the population of working women in five local government areas within Ibadan metropolis. The age of the participants was from 20-45years with a mean age of 28.80. Four standardized instruments; Ryff Psychological well-being Scale (r=0.73), Perceived Stress Scale (r= 0.71), Work-family Conflict Scale (r=0.75) and Utrecht Work Engagement Scale (r =0.84) was used. The statistical data analyses utilized are Pearson Product Moment Correlation and multiple regressions. Results indicate that psychological well-being negatively correlates with perceived stress (r = -.974, p<0.01), and work family conflict (r= -. 785 p<0.01), however, positive correlation was recorded with work engagement (r= .492, p<0.01). Result further showed a significant combined contribution of perceived stress, work-family conflict, and work, engagement on psychological well-being (yielding a coefficient of multiple regressions R= 0.605, multiple R2 = 0.366 and adjusted R2 =.355). Also, perceived stress, work-family conflict and work engagement are potent predictors of psychological well-being of working nursing mothers. The most potent factor was work engagement (β= .101, t = 7.051, P<0.01) work family conflict (β = -.074, t =- .2.437, P< 0.05) and perceived stress (β= - .974, t = -47.590, P<0.01). To this end, it is recommended that stress management trainings should be organized regularly to help working nursing mothers attain a balance in work and family life, mediate and reduce stress and ultimately improve the psychological well-being of working nursing mothers. Also, working conditions and organizational policies should also be tailored to encourage employee engagement as this will also boost performance and productivity